Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Given that f(x)=x'2−12x and g(x)=x+12, find(a) (f+g)(x)=(b) (f−g)(x)=c) (fg)(x)= (d) (f/g)(x)=

Given That Fxx212x And Gxx12 Finda Fgxb Fgxc Fgx D Fgx class=

Sagot :

Given:

[tex]\begin{gathered} f(x)=x^2-12x \\ g(x)=x+12 \end{gathered}[/tex]

Required:

To find

[tex]\begin{gathered} (f+g)(x) \\ (f-g)(x) \\ (fg)(x) \\ (\frac{f}{g})(x) \end{gathered}[/tex]

Explanation:

Now

[tex]\begin{gathered} (f+g)(x)=f(x)+g(x) \\ =x^2-12x+x+12 \\ =x^2-11x+12 \end{gathered}[/tex][tex]\begin{gathered} (f-g)(x)=f(x)-g(x) \\ =x^2-12x-x-12 \\ =x^2-13x-12 \end{gathered}[/tex][tex]\begin{gathered} (fg)(x)=f(x)g(x) \\ =(x^2-12x)(x+12) \\ =x^3+12x^2-12x^2-144x \\ =x^3-144x \end{gathered}[/tex][tex]\begin{gathered} (\frac{f}{g})(x)=\frac{f(x)}{g(x)} \\ \\ =\frac{x^2-12x}{x+12} \end{gathered}[/tex]

Final Answeer:

[tex]\begin{gathered} (f+g)(x)=x^2-11x+12 \\ (f-g)(x)=x^2-13x-12 \\ (fg)(x)=x^3-144x \\ (\frac{f}{g})(x)=\frac{x^2-12x}{x+12} \end{gathered}[/tex]